2005
DOI: 10.2486/indhealth.43.669
|View full text |Cite
|
Sign up to set email alerts
|

Model Development for Health Promotion and Control of Agricultural Occupational Health Hazards and Accidents in Pathumthani, Thailand

Abstract: In Thailand, agriculture is one of the major occupations; however, there is no comprehensive agricultural occupational health promotion and disease prevention model available. Objectives of this study were to empower farmers to study occupational health and safety situation in rice farming and to develop model to promote their health and prevent occupational health hazards among them. This participatory action research was performed in Tambol Klong 7, Klongluang district, Pathumthani, Thailand. The 24 rice far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…The major symptom among the farmers scattering seed and harvesting crops was numbness, suggesting that the exposure from scattering seed and harvesting crops affected the neuromuscular junction. These results are in agreement with those of Buranatrevedh and Sweatsriskul [35] who reported that the majority of abnormal physical health conditions among rice farmers were associated with the oral cavity, respiratory tract and musculoskeletal system. They also reported that musculoskeletal problems during seed the soaking/scattering and harvesting processes were caused by carrying heavy seed containers and lifting heavy rice sacks.…”
Section: Discussionsupporting
confidence: 83%
“…The major symptom among the farmers scattering seed and harvesting crops was numbness, suggesting that the exposure from scattering seed and harvesting crops affected the neuromuscular junction. These results are in agreement with those of Buranatrevedh and Sweatsriskul [35] who reported that the majority of abnormal physical health conditions among rice farmers were associated with the oral cavity, respiratory tract and musculoskeletal system. They also reported that musculoskeletal problems during seed the soaking/scattering and harvesting processes were caused by carrying heavy seed containers and lifting heavy rice sacks.…”
Section: Discussionsupporting
confidence: 83%
“…In Taiwan, community health development (CHD) has been initiated; this is a new approach to national community health care with a shift from 'traditional' research to 'participatory action' research (Huang and Wang, 2005). The history of participatory action research in Asia is relatively short, but one recent study in Thailand showed that this approach with farmers could create a real, sustainable model to promote their health and prevent occupational health hazards (Buranatrevedh and Sweatsriskul, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This was critical because input from these individuals would be necessary to further develop and, ultimately, help sustain such a programme (Buranatrevedh and Sweatsriskul, 2005;Mosavel et al, 2005). The increasing incidence and prevalence of diabetes and obesity and the importance of effectively addressing lifestylerelated diseases were undoubtedly a concern for community stakeholders at all levels.…”
Section: Discussionmentioning
confidence: 99%